Enhancing Routine Childhood Vaccination Uptake in the Cape Metropolitan District, South Africa: Perspectives and Recommendations from Point-of-Care Vaccinators - Elizabeth O. Oduwole; Christina A. Laurenzi; Hassan Mahomed; Charles S. Wiysonge (Vaccines, 2022)
Vaccination, and particularly childhood vaccination, is widely acknowledged as one of the greatest public health interventions in history. Nevertheless, challenges exist that threaten the progress of childhood vaccination in many parts of the world. We investigated challenges to vaccination experienced by point-of-care vaccinators in the Cape Town Metropolitan District (Cape Metro), and reported on their current and proposed efforts to combat these challenges. Semi-structured interviews were conducted with 19 vaccinators in 16 purposively selected healthcare facilities in the Cape Metro from September to November 2019. Interviews were transcribed and analysed using thematic and narrative analysis methods. Challenges of both the demand and the supply side of routine vaccination were reported by the study participants, as were contextual challenges such as community safety issues. Defaulting was the most common challenge encountered, reported by 16 of the 19 participants. The use of computerized appointment systems, the enlistment of community health workers to track down defaulters, and the use of certificates to incentivize caregivers are part of the creative ways of mitigating some of the challenges encountered by these vaccinators. Their insightful recommendations can positively influence the landscape of childhood vaccination uptake in the Cape Metro and beyond if adapted and applied.